DINAMIKA KEPRIBADIAN TOKOH UTAMA DALAM NOVEL HELLO KARYA TERE LIYE: KAJIAN PSIKOLOGIS SIGMUND FREUD - Noravida Ahmad; Elsa Mulya Karlina (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study aims to describe the personality dynamics of the main character in the novel Hello by Tere Liye based on the psychoanalytic perspective of Sigmund Freud. As a literary work, a novel not only presents a story but also portrays various aspects of human life, including inner conflicts and psychological conditions of the characters. The main character in Hello experiences emotional struggles, psychological pressure, and conflicts between personal desires and moral demands. This research employs a literary psychology approach focusing on Freud’s personality structure consisting of the id, ego, and superego. The method used is descriptive qualitative research with data collection techniques through library research and note-taking of relevant quotations from the novel. The results show that the personality dynamics of the main character are reflected in the dominance of the id through spontaneous instinctive impulses, the role of the ego as a mediator between desires and reality, and the function of the superego in controlling behavior based on moral values and social norms. The interaction of these three aspects creates inner conflicts that influence the attitudes and actions of the main character throughout the story. Therefore, the novel Hello reveals the complexity of human personality that can be examined deeply through a literary psychology approach.